Deskripsi Keanekaragaman Udang Air Tawar di Perairan Lentik dan Lotik Kabupaten Ogan Ilir, Sumatera Selatan - Stilaf Terbit Galih Walsandy; Arum Setiawan; Kodri Madang (Jurnal Penelitian Pendidikan IPA, 2026)
Freshwater shrimps are important components of inland aquatic ecosystems and contribute to biodiversity, nutrient cycling, and ecosystem stability. Despite their ecological importance, information regarding freshwater shrimp diversity in lentic and lotic ecosystems of Ogan Ilir Regency, South Sumatra, remains limited. This study aimed to identify freshwater shrimp species and describe their diagnostic morphological characteristics in contrasting freshwater habitats. Field sampling was conducted from November 2025 to January 2026 at six sampling stations representing three lentic and three lotic ecosystems. Specimens were collected using baited traps (bubu) and identified using standard taxonomic keys based on external morphological characteristics, including body shape, rostrum, cephalothorax, abdomen, telson, antennae, pereopods, pleopods, and body coloration. Three freshwater shrimp species belonging to the family Palaemonidae were identified, namely Macrobrachium lanchesteri, Macrobrachium rosenbergii, and Macrobrachium nipponense. Each species exhibited distinctive morphological characteristics that enabled reliable identification. Differences in species occurrence between lentic and lotic ecosystems indicate habitat-related variation in freshwater shrimp assemblages. This study provides baseline information on freshwater shrimp diversity in Ogan Ilir Regency and contributes to biodiversity inventories, taxonomic studies, and freshwater ecosystem conservation in South Sumatra.